Culinary Heritage and Materiality: Reconstructing Recipes from the Mānasollāsa - Sheemar, Tara (Advances in Social Sciences Research Journal, 2025)
This study examines the culinary heritage of the 12th-century Sanskrit encyclopaedia, the Mānasollāsa, from the detailed account of royal cuisine in the section known as annabhoga (‘the enjoyment of food’). The research reconstructs recipes as material-cultural artefacts, tracing the evolution of food traditions in the Indian subcontinent and highlighting the interplay between gastronomy, power, and identity in the medieval Deccan. By analysing the processes, materials, utensils, and specialist roles described in the text, the study reveals the sophistication of early Indian kitchens and the enduring influence of these practices on contemporary cuisine. The work also explores the socio-political significance of food, the diversity of ingredients—including both vegetarian and non-vegetarian dishes—and the integration of local and courtly traditions. Through detailed translations and reconstructions, the paper provides insight into the tangible and sensory aspects of medieval gastronomy, offering a valuable resource for historians, chefs, and anyone interested in the material culture of food.